2010
DOI: 10.1007/s11604-010-0491-4
|View full text |Cite|
|
Sign up to set email alerts
|

Structural and neurochemical evaluation of the brain and pons in patients with Wilson’s disease

Abstract: MRS is a noninvasive, valuable modality for detecting structural-neurochemical changes of the brain stem and deep gray matter in patients with WD. The contribution of DWI in these patients is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…No significant correlations were found between GM atrophy of BG and PM, which is inconsistent with a previous study (Dong et al, 2016). However, many previous studies have revealed the widespread alternations in BG which mainly lead to extrapyramidal symptoms such as tremors, ataxia, and dystonic syndrome (Ala et al, 2007;Algin et al, 2010). The possible interpretation is that PM impairment is easily masked by other symptoms (Lorincz, 2010) that did not manifest in structural damage in BG in the present study.…”
Section: Discussionmentioning
confidence: 44%
“…No significant correlations were found between GM atrophy of BG and PM, which is inconsistent with a previous study (Dong et al, 2016). However, many previous studies have revealed the widespread alternations in BG which mainly lead to extrapyramidal symptoms such as tremors, ataxia, and dystonic syndrome (Ala et al, 2007;Algin et al, 2010). The possible interpretation is that PM impairment is easily masked by other symptoms (Lorincz, 2010) that did not manifest in structural damage in BG in the present study.…”
Section: Discussionmentioning
confidence: 44%
“…Areas of symmetric hypointensity on T1-weighted images and symmetric hyperintensity on T2-weighted images were presented in the basal ganglia, thalamus, and brain stem [12]. Diffusion tenser imaging (DTI) is a noninvasive technique to measure microstructural organization in brain tissues in vivo, based on the properties of water diffusion [13].…”
Section: Introductionmentioning
confidence: 99%
“…Various organs, including the liver, kidneys, and brain, are impaired in untreated WD . Copper accumulation in the brain can induce changes such as myelin degeneration, gliosis, and profound neuronal loss . Among all brain structures (including the cerebellum), the gray matter in the basal ganglia is affected the most, followed by the brainstem (red nucleus and substantia nigra [SN]) and the cortex (especially the frontal lobes and the parieto‐occipital zones) .…”
mentioning
confidence: 99%
“…9 Copper accumulation in the brain can induce changes such as myelin degeneration, gliosis, and profound neuronal loss. 10,11 Among all brain structures (including the cerebellum), the gray matter in the basal ganglia [11][12][13][14][15] is affected the most, followed by the brainstem (red nucleus and substantia nigra [SN]) 16,17 and the cortex (especially the frontal lobes and the parietooccipital zones). 14,18 Additionally, emotion research has revealed that the psychiatric impairments of WD, including emotional lability, personality disorders, and mania, are caused by abnormalities in the limbic system 19 and basal ganglia.…”
mentioning
confidence: 99%